GEOMETRY OF GEMINGA ROTATION ACCORDING TO LIGHT CURVES IN GAMMA-REGION - Repin, S. V. (Одеські астрономічні публікації, 2017)
Light curves and spectrum of Geminga in a hard gamma region are investigated in this paper and their properties are discussed. The geometric parameters of pulsar rotation, such as the inclination angle of rotational axis, the angle between rotational and magnetic axes and the cone spread angle of gamma radiation are evaluated. All the results are based on the data of EGRET instrument.